Analisis Klausula Choice of Forum dalam Kontrak Standar E-Commerce di Indonesia: Kajian Berdasarkan Perspektif Perlindungan Konsumen - Saputra, Sarping (Jurnal Hukum & Pembangunan, 2025)
This research discusses choice of forum clauses in standard contracts on the five largest e-commerce platforms in Indonesia, namely Shopee, Tokopedia, Lazada, Bukalapak, and Blibli. The clause stipulates the mechanism and location of dispute resolution that automatically binds consumers when using the platform. In practice, these clauses tend to burden consumers, especially regarding access to fair dispute resolution. This research focuses on the compatibility of the choice of forum clause with the principles of consumer protection regulated in the Consumer Protection Law (UUPK). The results reveal that most e-commerce platforms use exclusive forms of choice of forum clauses, such as Shopee, Lazada, and Bukalapak, while Tokopedia and Blibli adopt non-exclusive forms. Although GCPL does not explicitly prohibit exclusive clauses, their application is considered to violate consumer rights because it complicates access to dispute resolution, which in this case contradicts the principles or principles in consumer protection, including the principles of justice, balance, and legal certainty. These conditions require serious attention, particularly through more stringent regulation of choice of forum clauses in standard contracts. The government is expected to formulate regulations that ensure clauses in standard contracts do not burden consumers, while business actors need to formulate fairer contracts.